INTERFERENSI BAHASA MANDAILING DALAM BAHASA INDONESIATULIS SISWA KELAS VIII MTS BAHARUDDIN KECAMATAN BATANG ANGKOLA KABUPATEN TAPANULI SELATAN - Fatwa Alama (Jurnal Edukasi Kultura: Jurnal Bahasa, Sastra dan Budaya, 2016)
Linguistic problem which is discussed in this research is aboutinterference, it is error which is caused by first language ( L1 ) to second language(L2). scmorphology, vocabulary,and syntax. But in this reseach, it is limited onmorphology. This research ains to de scribe Mandailing language interference inIndonesian writing from the word, kinds, and the caused. This research usesqualitative research and used descriptive method. The object of this research is theVIII grade students of MTS Baharuddin writing. The data of this research is thewords in sentence which contain of mandailing language morphological interferencein students’ writing. The instrument of this research is performance test. The datacollection is done by grouping the words which is interferenced into the workanalysis table. The result of the research shows that morphological interference ofMandailing in students’ Indonesian writing of theVIII grade students of MTSBaharuddin. First, there are Mandailing language interference in Indonesian include40 words from (1) such as ( nominal, verbal, adjective and conjunction), (2)affixation, (3) reduplication, and (4) composition. Second, productive interfernce,reseptive and psycological interference. Third, factors which caused the interferencein students’ writing are : (1) the influence of first language, (2) the lack ofunderstanding on the language which is used, and (3) unsuitable language teaching .so that, it can be concluded that based on the data found, the interference which isseen in the students’ writing is still fair, it means because the students are influencedby bilingual of the students.